Integrating GIS and statistical approaches to enhance allocation of highway patrol resources - Rezapour, Mahdi (International journal of police science & management, 2020)
Large truck crashes undermine the contribution of trucks to the U.S. economy due to the economic costs of the crashes. Wyoming has the highest truck crash rate and the lowest budget contribution for traffic enforcement in the USA. Because of the state’s intensive truck corridors, the Wyoming Highway Patrol (WHP) might not be able to use their resources efficiently. Previous studies have indicated that WHP performed better when they allocate their resources efficiently at the right locations and towards the right enforcements. This study used 4-year historical crash and enforcement data along Interstate 80 (I-80), which has the highest truck-related crash rate in Wyoming. Crash data were filtered to include truck crashes only. However, both truck and no-truck enforcements were included in the data because both could be at fault in truck crashes. This study used two approaches to help state policy-makers improve traffic safety on I-80. First, a statistical method was used to identify geometric variables contributing to allocated enforcement and truck crashes. Second, truck crashes and related enforcements were visually assessed using Geographical Information Systems (GIS) mapping. Crash data were disaggregated into the main driver actions of no improper driving, following too closely, improper lane change and driving too fast for the conditions. These driver actions accounted for more than 70% of all truck crashes on I-80. Related enforcements were also identified and disaggregated by driver actions. Disaggregated enforcements and crashes were visualized along the I-80 corridor using GIS maps to see if WHP allocated their resources efficiently. Cluster index, enforcement spatial coverage and mean density are some of the parameters used for the analyses. This study aimed to contribute to research on police effectiveness in reducing truck crashes, police innovation and the use of GIS applications in enforcement. This methodology can be used by other agencies to better allocate resources to improve traffic safety in most efficient ways.